Unsynchronized Driving Mechanisms of Spring and Autumn Phenology Over Northern Hemisphere Grasslands - Cong, Nan; Huang, Ke; Zhang, Yangjian (Frontiers in Forests and Global Change, 2021)
Global warming has impacted Northern Hemisphere (NH) grassland ecosystems to a great extent. Vegetation growing season length (GSL) has been extended by concurrent advances in spring green-up and postponements in autumn dormancy. However, the driving mechanisms of phenology are unclear as limited factors have been considered so far. Therefore, it is still elusive to what extent phenological changes shaped GSL. In this study, we used remote sensing normalized difference vegetation index (NDVI) to extract spring and autumn phenology of NH grasslands, and further explored the contribution of each phenophase to GSL through the coefficient of variation (CV) and contribution coefficient (CntC). We found that 65% of NH grasslands exhibited advanced start-of-season (SOS) and circa 58% showed delayed end-of-season (EOS) in the three decades. Changes in GSL was regulated more by EOS changes than by SOS changes, as evidenced by their respective 52% versus 48% CntC. As for the relationship between phenology and environmental elements, the causing factor analysis revealed that climatic factors (temperature, precipitation, and their interactions) played a dominant role in SOS variations, while environmental and internal factors exerted dominant effects on EOS. Also, interactions of temperature and precipitation contributed a higher variation of SOS than either of them individually. The differentiated factors controlling the two bounding ends of the growing season suggested that it is impossible for GSL to continue to extend without limits under global warming.